2022
DOI: 10.1126/sciadv.abn4564
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive life span is extended by targeted removal of fibrotic collagen from the mouse ovary

Abstract: The female ovary contains a finite number of oocytes, and their release at ovulation becomes sporadic and disordered with aging and with obesity, leading to loss of fertility. Understanding the molecular defects underpinning this pathology is essential as age of childbearing and obesity rates increase globally. We identify that fibrosis within the ovarian stromal compartment is an underlying mechanism responsible for impaired oocyte release, which is initiated by mitochondrial dysfunction leading to diminished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 82 publications
4
105
0
Order By: Relevance
“…This fibrotic trend was again observed in human samples, indicating that the phenomenon may be conserved across species during ageing (Manuel et al, 2019). A recent study has also shown that this ageing-associated reduction in female reproductive lifespan can be rescued by reversing collagen fibrosis in mouse ovaries (Umehara et al, 2022). It is known that fibrosis mechanically alters the organ by significantly increasing tissue stiffness (Wells, 2013).…”
Section: Interstitial Extracellular Matrixmentioning
confidence: 79%
“…This fibrotic trend was again observed in human samples, indicating that the phenomenon may be conserved across species during ageing (Manuel et al, 2019). A recent study has also shown that this ageing-associated reduction in female reproductive lifespan can be rescued by reversing collagen fibrosis in mouse ovaries (Umehara et al, 2022). It is known that fibrosis mechanically alters the organ by significantly increasing tissue stiffness (Wells, 2013).…”
Section: Interstitial Extracellular Matrixmentioning
confidence: 79%
“…MitoQ’s antioxidant function stems from inhibiting mitochondrial ROS and supporting ATP production, mitigating cellular oxidative stress (reviewed in [ 53 ]), while L-Carnitine increases the transport of fatty acids to the mitochondria or β-oxidation, improving mitochondrial function and reducing ROS levels [ 54 , 55 , 56 , 57 ]. The molecular target of BGP-15 is unknown; however, there is clear evidence that it affects mitochondrial bioenergetics [ 35 , 36 , 58 , 59 , 60 ]. BGP-15’s exact mechanism of action in sperm is currently unknown and under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrosis within the ovarian stroma results in anovulation, thereby causing fertility loss. The removal of fibrotic collagen from ovaries was demonstrated to prolong the female reproductive lifespan in mice ( 68 ).…”
Section: The Mechanisms Of Oma Per Se Leading To O...mentioning
confidence: 99%
“…Application of ammonium trichloro (dioxoethylene-o,o’) tellurate (AS101), a modulator of the PI3K-PTEN-Akt pathway, was proved to preserve ovarian reserve in mice ovaries with OMA by inhibiting the hyperactivation of primordial follicles ( 41 ). It was first reported that ovarian fibrosis in reproductive-aged mice could be reversed with antifibrosis drugs (pirfenidone and BGP-15) and thereby improved female fertility ( 68 ). The insights revealed in these therapeutic agents point to a prospective application in treating women with OMA accompanied by ovarian aging.…”
Section: New Treatment and Target Therapymentioning
confidence: 99%